Pharmacokinetic Virtual Screening and Molecular Docking Simulation for Evaluating Cytochrome P450 CYP3A4 Interactions Between Glibenclamide and Eurycoma longifolia Jack Extract - Isnaini, Puti; Marbun, Prajona; Purwantiningsih, Purwantiningsih; Nugroho, Agung Endro (Majalah Farmaseutik, 2025)
Type 2 diabetes mellitus is a chronic disease with a globally increasing prevalence. The treatment of diabetes mellitus involves oral blood glucose-lowering agents, including glibenclamide. Although effective, glibenclamide can cause severe hypoglycemia, leading people to often combine it with herbal remedies such as the root extract of Eurycoma longifolia (ELRE), commonly known in Malaysia and Indonesia as the herbal medicine Tongkat Ali. ELRE is known for its anti-diabetic effects through enhanced insulin sensitivity and antioxidant activity. However, the pharmacokinetic interaction between ELRE and glibenclamide, particularly involving CYP3A4, which metabolizes glibenclamide, has not been well studied. This study employed an in silico approach using pharmacokinetic virtual screening server, followed by molecular docking analysis to evaluate the potential interaction. The results indicated that nearly all of the investigated ELRE chemical constituents showed high predicted affinity, with two compounds, 14,15β-dihydroxyklaineanone and niloticin, exhibiting higher affinity than glibenclamide for CYP3A4. These compounds may act as competitive substrates, potentially influencing glibenclamide metabolism.